Knowledge-Based Front-End Engineering Design for Gas-Liquid Separator - Khang, Jeff @ Kuek Jun (2020)
Oil and gas industry is one of the largest and most dynamic industry in the world. In this industry, the project’s capital expenditure is frequently faced with enormous budget and schedule overruns. The complexity of the projects in oil and gas industry is consistently increasing, thus investing effort in reducing the budget and schedule are becoming more essential than ever before.